2021
DOI: 10.1159/000511610
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathologic Presentation of Primary Ocular Surface Tumors among Zambians

Abstract: <b><i>Aim:</i></b> This study aimed to characterize the clinical and pathologic presentation of ocular surface tumors (OSTs) and to more precisely differentiate the grades of ocular surface squamous neoplasia (OSSN) and benign lesions among Zambians. <b><i>Methods:</i></b> Two-hundred sixty-five Zambian patients presenting with ocular surface growths, suspicious for OSSN, were recruited between November 2017 and November 2019 to a cross-sectional study to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…Regarding the presentation of illness a growth of mass was the commonest accounting for 72% of all cases followed by foreign body sensation and proptosis. This nding is in alignment with a study from Zambia (17) and in contrary to the nding from Kano, Nigeria (18) and Malaysia (15) that showed that leukocoria and proptosis as prominent symptoms. This discrepancy from the current study stems from the later researches having a predominance of an intraocular location while conjunctival tumors are entertained more in the current study.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the presentation of illness a growth of mass was the commonest accounting for 72% of all cases followed by foreign body sensation and proptosis. This nding is in alignment with a study from Zambia (17) and in contrary to the nding from Kano, Nigeria (18) and Malaysia (15) that showed that leukocoria and proptosis as prominent symptoms. This discrepancy from the current study stems from the later researches having a predominance of an intraocular location while conjunctival tumors are entertained more in the current study.…”
Section: Discussionsupporting
confidence: 87%
“…We collected blood samples from all the patients for HIV, CD4, and plasma HIV viral load (VL) testing at recruitment, described previously ( 26 ). Most patients tested HIV positive (n = 177, 72.8%) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The University of Zambia Biomedical Research Ethics Committee (UNZABREC IRB # 015-05-17), the Zambia National Health Research Authority, and the University of Nebraska-Lincoln’s Institutional Review Board (IRB # 20170817442FB) approved this study. Using a cross-sectional study design ( Figure 1 ), we prospectively recruited patients 18 years and older who presented with an ocular surface tumor at the University Teaching Hospital in Lusaka, Zambia, between November 2017 and March 2020, as previously described ( 26 ). Consenting patients with a diagnosis of preinvasive and invasive OSSN and with adequate FFPE tissue for immunohistochemistry (IHC) were included in this analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Squamous cell carcinoma of the conjunctiva is the end-stage of a spectrum of disease referred to as ocular surface squamous neoplasia (OSSN). 2,5 Some conjunctival tumours are directly related to excessive exposure to the sun. Others, such as conjunctival squamous neoplasia (CoIN), have been found to be related to infection by human papillomavirus and HIV.…”
Section: Introductionmentioning
confidence: 99%